Aptamer and N-Degron Ensemble (AptaGron) as a Target Protein Degradation Strategy - Al Mazid, Mohammad Faysal; Shkel, Olha; Ryu, Eunteg; Kim, Jiwon; Shin, Kyung Ho; Kim, Yun Kyung; Lim, Hyun Suk; Lee, Jun-Seok (American Chemical Society, 2024)
Target protein degradation (TPD) is a promising strategy for catalytic downregulation of target proteins through various cellular proteolytic pathways. Despite numerous reports on novel TPD mechanisms, the discovery of target-specific ligands remains a major challenge. Unlike small-molecule ligands, aptamers offer significant advantages, owing to their SELEX-based systematic screening method. To fully utilize aptamers for TPD, we designed an aptamer and N-degron ensemble system (AptaGron) that circumvents the need for synthetic conjugations between aptamers and proteolysis-recruiting units. In our AptaGron system, a peptide nucleic acid containing an N-degron peptide and a sequence complementary to the aptamer was designed. Using this system, we successfully degraded three target proteins, tau, nucleolin, and eukaryotic initiation factor 4E (eIF4E), which lack specific small-molecule ligands. Our results highlight the potential of the AptaGron approach as a robust platform for targeted protein degradation.